(untitled) (Experimental biology, 2026)
This study examines various options for mixed cultures of bacteria of the genus Lactobacillus to create a lactose-free starter. The study emphasizes the importance of developing probiotic products for people with genetic or acquired lactase deficiency. The research methodology was based on the analysis of biocompatibility, acid-forming capacity and viability of Lactobacillus strains, which made it possible to develop a lactose-free starter based on mixed strains isolated from homemade fermented milk products of the Akmola region of Kazakhstan. The results showed that consortium №11, consisting of L. acidophilus (LB13) and L. rhamnoses (LR12) strains, is suitable for developing a technological scheme for the production of lactose-free starter. The purpose of the study is to use L. acidophilus and L. rhamnoses as starter cultures to develop a technological scheme for the production of a lactose-free starter. The practical significance of the work lies in the use of strains of L. acidophilus and L. rhamnoses strains as natural lactose-utilizing strains. The practical significance of the results of the work lies in the possibility its results in the food industry in order to produce lactose-free fermented milk drinks. The contribution of this work covers areas of scientific knowledge such as microbiology, food industry, medicine and biotechnology.